The Geology and Economic Potential of Gunung Terendum Area, Simpang Pulai. - binti Syed Mansor, Sharifah Nurfarhana (Universiti Teknologi PETRONAS, 2016)
This research is about the geology and economic potential of Gunung Terendum area, Simpang Pulai. This area is located within the popular tin mining area, Kinta Valley. Kinta Valley is comprise of extensive limestone hills and bordered by Triassic granite masses on both sides. Kinta Valley deposits are rich with concentration of alluvial cassiterite which covered the massive carbonate beds there. The study will include geological study that will contribute in generating the geological map of Gunung Terendum area at the scale of 1:10 000. The research includes some physical observation in the outcrops and detail geochemical analysis of the samples in the laboratory to identify the potential economic deposits in the area. This study will contribute to the understanding of the geology, as well as providing a great significance to the potential economic deposits of Gunung Terendum area.